Knowledge of Five-Tier Fish Farming - Punya Lertgrai, Dr.; ., .; ., . (International Journal of Engineering and Technology, 2018)
A study about the knowledge of five-tier fish farming was conducted in order to study:1) the learning process and Â knowledge about the five-tier fish farming, andÂ 2) the process of developing a five-tier fish farming model using qualitative research. By analysing and synthesising, the researcher tried to develop knowledge and lessons on how to solve farmersâ€™ problems. Using knowledge about the nature of the fish, the aim was to develop a fish farming model in the target area. The research found that five-tier fish farming is well suited to lowland conditions when there is a canal nearby and family members can be used. Knowledge about the right management style will enable farmers to live well in their community. By learning, observing, monitoring and investigating phenomena happen and using the obtained knowledge to develop continuously and with academic and government support, farmers can obtain their goals. Educational field trips, listening to new ideas and analysis of talks with knowledgeable people will also be useful. The model obtained in this way will have to be tried out and periodically evaluated with input from the grassroots. Knowledge obtained through small-scale experiments can then be used on a bigger scale in order to expand the results. Small experiments in five-tier fish culture can be used as the learning base for the process of naturally raising fish. The learning process must be self-directed through development and evaluation of knowledge and wisdom. This has to be done by observation, analysis and self-management of various models. The results of any evaluation should be discussed with knowledgeable experts. Then turn back to the development stage and to further trials. Development should be analysed using the Spiral Model to achieve better results and to finally arrive at a form of five-tier fish farming that is suitable to the environment of each area.Â Â